Plant extracts from Cameroonian medicinal plants strongly inhibit hepatitis C virus infection in vitro - Galani, Borris R. T.; Sahuc, Marie-Emmanuelle; Njayou, Frederic N.; Deloison, Gaspard; Mkounga, Pierre; Feudjou, William F.; Brodin, Priscille; Rouillé, Yves; Nkengfack, Augustin E.; Moundipa, Paul Fewou; Séron, Karin (Frontiers in Microbiology, 2015)
According to some recent studies, Cameroon is one of the sub-Saharan African countries most affected by hepatitis C, with low access to the standard therapy based on the combination of pegylated interferon and ribarivin. A first ethnobotanical survey, conducted in the Western region of Cameroon, reported the use of several medicinal plants in traditional medicine for the healing of liver-related disorders. Crude organic extracts of five plants surveyed were prepared and their effect against HCV infection investigated. The HCV JFH1 strain cell culture system HCVcc was used. The antiviral activity was quantified by immunofluorescent labeling of HCV E1 envelope protein at 30h post-infection in the presence of the plant extracts. Active compounds were then tested in time course infection experiments. Dose-response and cellular toxicity assays were also determined. Three extracts, methanol extracts from roots of Trichilia dregeana, stems of Detarium microcarpum and leaves of Phragmanthera capitata, showed anti-HCV activity, with half-maximal inhibitory concentration of 16.16 µg/mL, 1.42 µg/mL and 13.17 µg/mL, respectively. Huh-7 cells were incubated with the extracts for 72 h and it appears that T. dregeana extract is not toxic up to 200 µg/mL, D. microcarpum up to 100 µg/mL and P. capitata up to 800 µg/mL. All the three extracts showed a strong inhibition of HCV entry and no effect on replication or secretion. Taken together, these results showed that extracts from Cameroonian medicinal plants are promising sources of anti-HCV agents.